The Relationship Between Late Morbidity and Dose–Volume Parameter of Rectum in Combined Intracavitary/Interstitial Cervix Cancer Brachytherapy: A Mono-Institutional Experience - Zhang, Ning; Liu, Ying; Han, Dongmei; Guo, Xin; Mao, Zhuang; Yang, Wei; Cheng, Guanghui (Frontiers in Oncology, 2021)
Purpose: To establish a dose volume–effect relationship for predicting late rectal complication (LRC) in locally advanced cervical cancer patients treated with external beam radiotherapy (EBRT) followed by combined intracavitary/interstitial brachytherapy (IC/IS-BT). Materials and Methods: A retrospective analysis was performed in 110 patients with locally advanced cervical cancer who underwent definitive radiotherapy combined with IC/IS-BT from July 2010 to September 2018. We report the 90% of the target volume receiving the minimum dose for high risk clinical target volume (HR-CTV D90) and intermediate risk clinical target volume (IR-CTV D90), and the minimum doses to the most exposed 0.1, 1, and 2 cm³ (D0.1cm³, D1cm³, and D2cm³) doses at the International Commission on Radiation Units and Measurements (DICRU) for organs at risk (OARs). The total dose of EBRT plus brachytherapy was transformed to the biologically equivalent dose in 2 Gy fractions(EQD2) with α/β of 3 Gy using the linear quadratic model. The morbidity was scored according to the Radiation Therapy Oncology Group (RTOG). The Probit model was used to establish a prediction model on rectum between the organs at risk for dose and LRC. The receiver operating characteristic (ROC) curve was used to evaluate the predictive value of dose volume parameters for LRC. Results: The median follow-up time was 72.3 months. The Probit model showed significant relationships between D1cm³, D0.1cm³ and the probability of grade (G )1-4, G 2-4 rectal events at 1 year, and between D1cm³ and the probability of G 2-4 rectal events at 3 and 5 years. The doses values for 10% complication rates (ED10) of D1cm³ were 74.18 (70.42-76.71) GyEQD2, 67.80 (59.91, 71.08) GyEQD2, 66.37 (52.00, 70.27) GyEQD2 for G 2-4 with rectal morbidity at 1, 3 and 5 years, respectively. Conclusion: Our study proved that D1cm³ and D0.1cm³ were considered as useful dosimetric parameters for predicting the risk of grade (G)1-4 and G2-4 LRC at 1-year, and D1cm³ might be an indicator for predicting G2-4 LRC at 3/5year. The patients with rectal D1cm³>66.37-74.18GyEQD2 are should be closely observed for G2-4 LRC.